THE EFFECT OF BULLYING CONSUMPTION ON BULLYING BEHAVIOR AND EXPERIENCE OF HIGH SCHOOL STUDENTS: A CASE STUDY IN SMK 49 NORTH.JAKARTA - Soeryowati, P Lestari (Universitas Mercu Buana, 2025)
Schools are very influential in educating the younger generations. Not only creating a good generation, it turns out that schools can also be a place for violence, whether by teachers against students, students against teachers, or students against other students. Acts of violence committed by students in schools are increasingly heard and very worrying. This is evidence of the loss of human values and moral values. One that often occurs in the school environment today is Bullying. The word Bullying comes from English, namely from the word bull which means bull. In Indonesian, etymologically the word bully means to intimidate, while in terminology according to the definition of bullying according to Rigby (1994) is